Ambivalent Attitudes to Regional Dialects in Hungary: Investigating Students and Teachers - PARAPATICS, ANDREA (Indonesian Research Journal in Education |IRJE|, 2019)
The paper presents two connecting studies on the linguistic mentality of the Hungarian society to regional dialects. The focus of the study is to find an explanation of the problem that Hungarians learn to respect diversity, although, misbeliefs and standard-based culture usually lead to debates in communication or even to linguicism. The main hypotheses are: white-collar-to-be students cannot apply what they learnt about dialects, therefore, many corrections are motivated by regionalisms of which they are not aware, and it is all rooted in problems of teacher training and practice related to language variability. 548 university students 170 teachers in middle and high schools were asked in questionnaires about their language attitudes and everyday experiences and practice. The results highlighted: while tolerant attitudes are represented theoretically, standard-based practice suggests negative lessons about dialects.